SOSIALISASI CALON INSTRUKTUR POS PAUD DI KELURAHAN SAMPANGAN KECAMATAN GAJAH MUNGKUR SEMARANG - Munawir IKIP PGRI Semarang; Soegeng Partono; Rivanna Citraning R; Eko Retno M; Dias Andris Susanto (E-Dimas: Jurnal Pengabdian kepada Masyarakat, 2011)
Abstract ?é?á Nowadays PAUD/ pre-school education is really important and urgent to be conducted in any villages or kampongs. Sampangan village Gajah Mungkur Semarang is one the villages that needs to be explored and held by the team of community service. Implementing PAUD is actually already arranged in UU no. 20/ 2003. By that rule, the team try to give some programs such as; socialization and training about what is PAUD, how to be PAUD instructors, how to teach children well. The training was held for 2 days started on 4-5 December 2010 at 08.00 am ?óÔé¼ÔÇ£ 04.00 pm, located in?é?á Sampangan Village the office hall, Gajahmungkur Semarang. ?é?áThe main purpose of this program is holding and socializing PAUD in that village in order to have more skills for the instructors in teaching children more interesting. Team used some methods in this training such as giving speech, discussion, simulation, and practice. By having those methods, it is hoped that the candidates of PAUD teachers will understand and comprehend about the materials dealing with what is PAUD and how to teach children more effective and interesting. ?é?á Key words: PAUD, socialization, instructor ?é?á